Crystallographic orientation-dependent strain hardening in a precipitation-strengthened Al-Cu alloy. (15th February 2021) - Milligan, Brian; Ma, Dong; Allard, Lawrence; Clarke, Amy; Shyam, Amit
Abstract: While the strengthening of Al-Cu alloys due to precipitation has been extensively studied, the effect of crystallographic orientation of the matrix and precipitates, as well as precipitate morphology, on the strain hardening behavior is not well understood. Here we investigate this effect with in situ neutron diffraction during deformation of an Al-Cu alloy (206) after multiple aging treatments. Precipitate-dislocation interactions were found to change from precipitate shearing for microstructures predominantly containing GPI and θ′′ precipitates to Orowan looping for microstructures with primarily θ′ and θ precipitates. Notably, significant anisotropy in strain hardening behavior was observed when θ′ precipitates were present, which was attributed to crystallographic orientation dependent load transfer from the Al matrix to the θ′ precipitates. The anisotropic load transfer is hypothesized to be caused by the extent of rotation of high aspect-ratio θ′ precipitates, owing to dislocations looping around them during plastic deformation of the matrix. Predictions from an analytical model describing the anisotropic magnitude of load transfer from precipitate rotation agree well with experimental results, successfully validating the precipitate rotation hypothesis and explaining the anisotropic strain hardening behavior. This model allows for the prediction of stresses separately in the precipitate and matrix phases as a function of crystallographic orientation, only given the bulk mechanical properties. Graphical abstrcats: Image, graphical abstract